ANALISIS EXPERIENTAL MARKETING TERHADAP MINAT BELI ULANG PADA TOKOPEDIA DI PANGKALPINANG - Dea Martha; Nanang Wahyudin; Dian Prihardini Wibawa (PT. Hasba Edukasi Mandiri, 2025)
The growing competition in the e-commerce industry demands digital platforms to offer not only transactional convenience but also meaningful and enjoyable shopping experiences. As one of Indonesia’s largest e-commerce platforms, Tokopedia needs to implement marketing strategies that foster customer loyalty, particularly through Experiential Marketing. This study aims to analyze the influence of five dimensions of Experiential Marketing (Sense, Feel, Think, Act, and Relate) on the Repurchase Intention of Tokopedia users in Pangkalpinang City. A quantitative approach was adopted using descriptive and verificative methods. Data were collected through questionnaires distributed to 100 active Tokopedia users and analyzed using multiple linear regression. The results show that all five dimensions of Experiential Marketing have a positive and significant influence on Repurchase Intention. Feel and Relate dimensions contributed most dominantly, followed by Think and Sense. The Adjusted R Square value of 0.772 indicates that 77.2% of the variation in Repurchase Intention is explained by these variables, supported by a strong correlation (R = 0.885). These findings affirm that positive customer experience through Experiential Marketing plays a vital role in strengthening loyalty and encouraging repeat purchases on digital commerce platforms.